An integrated approach for dynamic customer requirement identification for product development. Issue 4 (21st April 2019) - Dou, Runliang; Li, Wei; Nan, Guofang
ABSTRACT: Due to the requirement diversity of customers, corporations must produce products that match customer expectations and maximize their revenue. Hence, when they are planning to launch new products, dynamic customer requirements should be focused to predict customer's tastes in target time. With the accurate sense of customer requirements, companies can make response directly to these requirements to improve their products. In order to tackle the problem, the proposed approachobtained customer requirements using a Fuzzy Kano Model (FKM) and Benchmarking theory for the extent of satisfaction improvement of each product attribute from the aspect of customer perception and competitor performance can be both measured. Furthermore, the study used optimized Grey model to identify dynamic customer requirements for its low demand for data size. And House of Quality (HoQ) was employed to calculate the optimal improvement plan. A comparison experiment was conducted to show the effectiveness of the approach. With the approach applied to company, customer requirements can be accurately grasped and companies can save time and cost to design and manufacture products which can match customer's changing tastes.